'These had most to give': Kathleen Scott's sculpture at the Scott Polar Research Institute, Cambridge. (2nd September 2013) - Stocker, Mark
ABSTRACT: The bronze sculpture variously known as These had most to give, Aspiration and Youth, stands in the forecourt of the Scott Polar Research Institute (SPRI) in Cambridge, and functions as a memorial to the British Antarctic Expedition polar party of 1911–1912. It is one of the most important works by Kathleen Scott, wife of Robert Falcon Scott, and a prominent and prolific sculptor. Originally intended as a war memorial and dating from 1922–1923, it received critical acclaim and was exhibited widely. Ten years later Kathleen Scott offered the sculpture to the SPRI to accompany its new building. The institute's committee of management wished to reject the gift, however, as its members considered it too successful in conveying 'death and martyrdom and in general the tragic side of Polar work', as Frank Debenham stated, rather than scientific research and discovery. After prolonged discussions with the institute's architect, Herbert Baker, who admired Kathleen Scott and this work, it was finally accepted and installed as inconspicuously as possible. This article reconstructs the historical background to the sculpture and the controversy that surrounded it, using primary source material. The relevance of the objections to the sculpture, as well as its positive qualities, are also briefly examined from a modern perspective.